The Moderating Role of Taxation Technology on the Relationship between Tax Rates and Taxpayer Perceptions of Tax Evasion - Putra, M Doni Permana; Sutrisni, Ketut Elly (Jurnal Ilmiah Akuntansi & Bisnis, 2025)
This study investigates the effect of tax rates on taxpayer perceptions of tax evasion and examines the moderating role of taxation technology in this relationship, grounded in the Theory of Planned Behavior. Employing a quantitative approach, this research collected primary data through questionnaires from a sample of 100 individual taxpayers at KPP Pratama Denpasar Barat. The data were analyzed using Moderated Regression Analysis (MRA). The results indicate that tax rates have a significant positive effect on the perception of tax evasion, suggesting higher rates increase the perceived viability of evasion. However, the study's primary finding reveals that taxation technology significantly weakens this positive relationship, acting as a negative moderator. These findings suggest that while higher tax rates may increase the incentive to evade, a robust technological infrastructure serves as an effective deterrent by increasing the perceived difficulty and risk of evasion. As a key policy implication, these results strongly advise authorities to prioritize and accelerate investment in the digital transformation of tax administration, as this technology is a critical tool for enhancing voluntary compliance by mitigating the perceived incentives for evasion.